The last refuge - Coes, Ben (Coes, Ben. Dewey Andreas novel., 2012)
"Off a quiet street in Brooklyn, New York, Israeli Special Forces commander Kohl Meir is captured by operatives of the Iranian secret service, who smuggle Meir back to Iran, where he is imprisoned, tortured, and prepared for a show trial. What they don't know is that Meir was in New York to recruit Dewey Andreas for a secret operation. Andreas, a former Army Ranger and Delta, owes his life to Meir and his team of Israeli commandos. Now, to repay his debt, Andreas has to attempt the impossible: to both rescue Meir from one of the world's most secure prisons, and to find and eliminate Iran's nuclear bomb before it's deployed -- all without the help or sanction of Israel or America."--from Publisher's information.